2016
DOI: 10.1002/clen.201500555
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Desorption of Copper and Cadmium in a Contaminated Soil Affected by Soil Amendments

Abstract: Sorption and desorption processes control the bioavailability of heavy metals in the environment. Soil incubation and batch experiments were conducted to evaluate the effects of soil amendments on sorption, and desorption of Cu 2þ and Cd 2þ in a contaminated acidic paddy soil. The study showed that limestone and silicon fertilizer increased Cu 2þ and Cd 2þ sorption 2.43-and 1.13-fold, which was higher than calcium magnesium phosphate, Chinese milk vetch, pig manure, and peat. The Freundlich equation fitted sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
4
13
0
Order By: Relevance
“…Based on research conducted thus far (Arias et al 2002; Aşçı 2012; Covelo et al 2007; Li et al 2016b), it can be concluded that for soils experimental data are usually best fitted to FM, as observed in the present study. For example, studying the sorption of Cd, Cu, Ni, Pb, Zn by six soils Covelo et al (2007) found that the data were closely correlated mostly with FM, with few cases of the correlation to LM (Covelo et al 2007).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Based on research conducted thus far (Arias et al 2002; Aşçı 2012; Covelo et al 2007; Li et al 2016b), it can be concluded that for soils experimental data are usually best fitted to FM, as observed in the present study. For example, studying the sorption of Cd, Cu, Ni, Pb, Zn by six soils Covelo et al (2007) found that the data were closely correlated mostly with FM, with few cases of the correlation to LM (Covelo et al 2007).…”
Section: Resultssupporting
confidence: 75%
“…For example, studying the sorption of Cd, Cu, Ni, Pb, Zn by six soils Covelo et al (2007) found that the data were closely correlated mostly with FM, with few cases of the correlation to LM (Covelo et al 2007). FM was reported as more suitable for adsorption of PTEs by soils also by other authors (Arias et al 2002; Aşçı 2012; Li et al 2016b).…”
Section: Resultssupporting
confidence: 52%
“…The evaluation of 2b for Cu 2+ -sensing in soil was conducted using a water extraction [37] of roadside soil samples collected in the western parts of Melbourne, Victoria, Australia. Fluorescence titrations generated using 2b were compared against the industry standard of ICP-MS quantification [38].…”
Section: Resultsmentioning
confidence: 99%
“…To study the effect of biopolymer-bentonite composite addition on heavy metal adsorption by soils, a procedure (Xiong et al 2005;Tsadilas et al 2009;Uchimiya et al 2011;Li et al 2016;Bogusz et al 2017) similar to the aqueous system was followed. To 1 g soil, 0.05 g chitosan-bentonite composite was added, and the mixture was incubated for a fortnight at room temperature (25 o C).…”
Section: )mentioning
confidence: 99%